KEBIJAKAN LUAR NEGERI INDONESIA UNTUK AFGHANISTAN PASCA-KEJATUHAN KABUL TAHUN 2021 DARI PERSPEKTIF KONSTRUKTIVISME - Sairwona, Musa Derek (Universitas Pelita Harapan, 2024)
The fall of Kabul in 2021 and the return of Taliban to leadership created dilemma for various countries’ foreign policy, including Indonesia. For Indonesia, diplomatic relations with Afghanistan which has been built since their independence must be maintained. On the other side, the way Taliban take over the leadership and various main values of Taliban are contradictory with international values and norms, which makes it difficult to acknowledge the government of Taliban. In facing this dilemma, Indonesia keeps the relationship with Afghanistan even though Indonesia has not acknowledged the government of Taliban. Indonesian foreign policy towards Afghanistan can be seen in the form of educational assistance for the people of Afghanistan, especially higher education access for woman, Using the Constructivism perspective, this research finds out that identity, values, and norms acknowledged by Indonesia as a democratic country with the most Muslim population in the world are sharpening its foreign policy. In addition, the leadership of Indonesia Minister of Foreign Affairs Retno Marsudi as the first woman to be the Minister of Foreign Affairs becomes one of the most important factors that affects the choices of Indonesian foreign policy. Retno Marsudi is well known for her priority of the importance of education for woman and the value of global Islamic solidarity.